Assessment of the quality of life of patients with type 2 diabetes mellitus with diabetic foot syndrome after reconstructive surgery (Texas Journal of Medical Science, 2022)
Diabetes mellitus (DM) is a paramount and rising medical challenge in both industrial and emerging nations. It represents a serious medical and social problem, which is due not only to its high prevalence, chronic course, which determines the accumulation of a contingent of patients with diabetes, but also to a large number of complications and a high degree of disability.